Sustained inflation: Prophylactic or rescue maneuver?. Issue 3 (June 2016) - Lista, G.; Cavigioli, F.; Castoldi, F.; Zimmermann, L.J.I.
Summary: Application of nasal continuous positive airway pressure (nCPAP) in the delivery room is a valid alternative to mechanical ventilation in the management of respiratory failure of preterm infants, with reduced occurrence of bronchopulmonary dysplasia and death. nCPAP at birth is still burdened by a high failure rate. Sustained inflation appears to be an intriguing approach to allow the respiratory transition at birth by clearing the lung fluid, thus obtaining an adequate functional residual capacity. This may enhance nCPAP success. Sustained inflation reduces the need for mechanical ventilation in the first 72 h of life, with no changes in the incidence of bronchopulmonary dysplasia and death. The efficacy of sustained inflation seems to be related to the presence of open glottis with active breathing of the infant. Further studies are needed to recommend the application of sustained inflation during delivery room management of preterm infants at risk of respiratory distress or with clinical signs of respiratory failure.